Correction: The evaluation of a web-based tool for measuring the uncorrected visual acuity and refractive error in keratoconus eyes: A method comparison study. - Marc B Muijzer; Janneau L J Claessens; Francesco Cassano; Daniel A Godefrooij; Yves F D M Prevoo; Robert P L Wisse (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0256087.].